THE IMAGE OF "LOVER-MISTRESS-RIVAL" IN EXAMPLES OF DIVINE SOURCES, MYTH AND NATIONAL FOLKLORE - Yulduz ZIYAYEVA; Serpil Yazıcı Sahin (Journals Park Publishing, 2024)
In the article, "Lover-mistress-rival" is analyzed in detail in divine sources, myths, and examples of national folklore. In this case, it is scientifically proved that the genesis of the image-triad is in divine sources, that it passed into myths, came in a distorted and changed form, that it went from an individual image to a general one in the samples of national folklore, and that it rose to the scale of the nation.
Keywords: divine sources, myth, epic, image, historical-traditional image, image of lover-mistress-rival, meeting-separation-visual motifs.